Penerapan Activity Based Costing System Dalam Menentukan Biaya Overhead - Monika Handayani; Arisa Aulia Rahmi; Zaskia Aliza; Zulchaidir Ali (Indonesian Journal of Applied Accounting and Finance, 2023)
UMKM costs have an important role in calculating the total production costs of a product or service, so management is required to calculate UMKM costs correctly in determining the selling price of a product or service as well as in analyzing profit per unit. This research is aimed to determine the amount of UMKM costs in the Katuju Laundry business. The method used to calculate UMKM costs is an Activity-Based Costing (ABC). The results of this research found that there were distorted costs due to the traditional cost assignments that had been used so far. Therefore, this research provides recommendations on the importance of more accurate cost allocation methods to improve decision making and increase cost control